Western Foreigners on the Russian Service and Royal Doctors in the Time of Ivan the Terrible - T. V. Tchernikova (Vestnik MGIMO-Universiteta, 2012)
The article is devoted to an examination of a question of the use of different western experts on the Russian service in the XVI century. The author tries to find out in what areas and what kind of foreign experts were used in Russia at the times of Ivan IV; what were the reasons for the use of the Western European experts as well as results and significance of this phenomenon. Changes in the position of immigrants from the Western Europe during one and a half centuries are also examined.